Outcome predictors of immune-mediated necrotizing myopathy—a retrospective, multicentre study. (12th January 2022) - Wang, Jeremy X; Wilkinson, Michael; Oldmeadow, Christopher; Limaye, Vidya; Major, Gabor
Abstract: Objectives: Evidence-based treatment protocols are currently lacking for immune-mediated necrotizing myopathy (IMNM). In this multicentre retrospective study, we examined baseline clinical characteristics and treatment variables that may predict short-term outcomes of patients with IMNM. Methods: Muscle biopsies from the John Hunter Hospital and the Royal Adelaide Hospital obtained between 2012 and 2019 were reviewed at a single laboratory at South Australia Pathology. All biopsies with histological features of IMNM were identified. Demographics of study subjects, clinical information and myositis-specific antibody status were recorded along with muscle strength, serum creatine kinase (CK) and treatment regimens at baseline and 3 and 6 months. Primary outcome measures were muscle strength and serum CK at 3 and 6 months. Mixed-effects regression models in a Bayesian framework were performed using the R statistical package. Results: Female sex, older age, initial prednisone dose and i.v. methylprednisolone were associated with greater improvement in serum CK. In patients with moderate–severe disease at baseline, early IVIG was associated with greater improvement in hip flexor strength at 6 months. Conclusion: Early IVIG was associated with clinical improvement in the short-term follow-up in IMNM. Female sex, older age, initial oral prednisone dose and initial use of i.v. methylprednisolone were associated with better biochemical improvement.